2022
DOI: 10.1039/d2nr03292a
|View full text |Cite
|
Sign up to set email alerts
|

Tailored mechanosensitive nanogels release drugs upon exposure to different levels of stenosis

Abstract: Owing to the unhealthy lifestyle and genetic susceptibility of today’s population, atherosclerosis is one of the global leading causes of life-threatening cardiovascular diseases. Although a rapid intervention is required for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 54 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…demonstrated the sensitivity of nanogels containing different poly(ethylene glycol) diacrylate concentrations to different shear stress levels. [ 133 ] Similarly, simvastatin acid (SA)‐loaded cross‐linked dendrimer nanoparticles (SA PAM) were created by Shen et al. and attached to the surfaces of RBCs resulting in the formation of SA PAM@RBCs.…”
Section: Therapeutic Strategies For Asmentioning
confidence: 99%
See 2 more Smart Citations
“…demonstrated the sensitivity of nanogels containing different poly(ethylene glycol) diacrylate concentrations to different shear stress levels. [ 133 ] Similarly, simvastatin acid (SA)‐loaded cross‐linked dendrimer nanoparticles (SA PAM) were created by Shen et al. and attached to the surfaces of RBCs resulting in the formation of SA PAM@RBCs.…”
Section: Therapeutic Strategies For Asmentioning
confidence: 99%
“…Kimna et al demonstrated the sensitivity of nanogels containing different poly(ethylene glycol) diacrylate concentrations to different shear stress levels. [133] Similarly, simvastatin acid (SA)-loaded cross-linked dendrimer nanoparticles (SA PAM) were created by Shen et al and attached to the surfaces of RBCs resulting in the formation of SA PAM@RBCs. [134] While 61.3% of the SA PAM desorbed from RBCs in response to a high shear stress stimulus (100 dynes per cm 2 ), only 12.4% detached from RBCs under low shear stress (20 dynes per cm 2 ).…”
Section: Shear Stress-responsive Strategiesmentioning
confidence: 99%
See 1 more Smart Citation